(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Smoking has devastating and often fatal effects on human health. It has a wide range of harmful effects on the body, even on organs like the liver that don't come into direct touch with the smoke. On the liver, it causes three primary harms: toxic effects (both direct and indirect), immunological effects, and oncogenic consequences. The cytotoxic potential of the chemicals produced by smoking might contribute to liver cell damage. The purpose of this research was to provide a broad review of how smoking affects the enzymes and functions of the liver.